Religious institution with social roles: revival of waqf in Kerala - Muhsin, Sayyed Mohamed (2022)
The deliberations on the role of Maqāṣid Sharīʿiah in modifying the governance of waqf are found vital as they connect the dots in finding the shortcoming of the existing system of waqf management and resolve the problems The implementation of Maqāṣid guarantees the attainment of sustainable development goals and ultimate success from material and spiritual aspects This work explores the vitality, potentiality and inevitability of maqāṣidic governance to the waqf administration in Kerala.